2019
DOI: 10.1096/fj.201900561r
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of syndecan‐2 in proximal colon correlates with acute inflammation

Abstract: We previously reported that syndecan‐2 expression is increased on the colonic epithelium during chronic inflammation. Here, we report that syndecan‐2 exhibits a different pattern of site‐specific colonic expression during acute inflammation. Syndecan‐2 expression was up‐regulated predominantly in the proximal colon of dextran sulfate sodium‐induced colitis mice. The colitis‐associated up‐regulation of syndecan‐2 was barely detected in Rag‐1−/− (recombination activating gene 1 knockout) mice under colitis‐induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
1
10
1
Order By: Relevance
“…To further investigate the direct role of MMP-7 in the extracellular shedding of syndecan-2 in colon tissues, we collected colonic tissues from acute DSS-induced mice and treated these tissues with MMP-7 in the absence or presence of an MMP inhibitor ( Figure 6 ). Consistent with a previous report, 24 we found that acute inflammation mediated by DSS induced expression of syndecan-2 predominantly in the proximal colon, but not detectable amounts of MMP-7 in the proximal colon ( Figure 6A ). The direct application of MMP-7 enzyme to ex vivo-cultured proximal colon tissues expressing syndecan-2 increased the levels of shed syndecan-2 in the tissue culture media, and this was inhibited by cotreatment with 500 nM MMP-7 inhibitors (GM6001) ( Figure 6B ), further confirming that MMP-7 mediates the extracellular domain shedding of syndecan-2 in colon tissues.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…To further investigate the direct role of MMP-7 in the extracellular shedding of syndecan-2 in colon tissues, we collected colonic tissues from acute DSS-induced mice and treated these tissues with MMP-7 in the absence or presence of an MMP inhibitor ( Figure 6 ). Consistent with a previous report, 24 we found that acute inflammation mediated by DSS induced expression of syndecan-2 predominantly in the proximal colon, but not detectable amounts of MMP-7 in the proximal colon ( Figure 6A ). The direct application of MMP-7 enzyme to ex vivo-cultured proximal colon tissues expressing syndecan-2 increased the levels of shed syndecan-2 in the tissue culture media, and this was inhibited by cotreatment with 500 nM MMP-7 inhibitors (GM6001) ( Figure 6B ), further confirming that MMP-7 mediates the extracellular domain shedding of syndecan-2 in colon tissues.…”
Section: Resultssupporting
confidence: 93%
“… 21 We also recently reported evidence suggesting that syndecan-2 expression might be increased during the inflammatory response. 20 , 24 Here, we further investigated whether syndecan-2 shedding occurs during inflammation. First, acute inflammation on syndecan-2 shedding was assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both syndecan-1 and IL-17 are shown to be increased in nasal polyps, a chronic inflammation in the nasal cavity (48). Syndecan-2 expression is elevated in endothelial cells during inflammation, where they can directly bind with cytokines (e.g., CXCL-8) and induce the expression of other cytokines (e.g., IL-1α, IL-17A + ) (25,49). The silencing of syndecan-4 in HUVEC cells resulted in an elevation of pro-inflammatory factors (e.g., CXCL-8), which suggests that a loss of syndecan-4 may result in an aggravated inflammatory response.…”
Section: Syndecans In Inflammationmentioning
confidence: 99%
“…In a recent study, the authors reported an upregulation of syndecan-2 in response to acute-induced inflammation in mice colons. This study also reports high expression levels of syndecan-2 in other inflammation-associated diseases, like colitis and sepsis, as this high-level expression is a good marker for acute inflammation and acute inflammation-associated diseases [87]. Another study using human umbilical vascular endothelial cells (HUVECs) demonstrated that syndecan-4 expression increased after inducing inflammation using lipopolysaccharides (LPS) and IL-1 (which together mimic a bacterial infection and a general inflammatory condition).…”
Section: Syndecan Shedding During Wound Healingmentioning
confidence: 57%